2005
DOI: 10.4049/jimmunol.174.7.3941
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Induction of CD4 T Cell Tolerance and CD8 T Cell Immunity by Semimature Dendritic Cells

Abstract: Previous studies suggested that depending on their maturation state, dendritic cells (DC) could either induce T cell tolerance (immature and semimature DC) or T cell activation (mature DC). Pretreatment of C57BL/6 mice with encephalitogenic myelin oligodendrocyte glycoprotein (MOG)35–55 peptide-loaded semimature DC protected from MOG-induced autoimmune encephalomyelitis. This protection was mediated by IL-10-producing CD4 T cells specific for the self Ag. Here we show that semimature DC loaded with the MHC cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 48 publications
3
30
0
1
Order By: Relevance
“…However, some reports have demonstrated that DC are able to induce not only immunity but also immune tolerance, depending on the stage of their maturation. In fact, some papers have demonstrated that certain types of DC have potential for the treatment of autoimmune diseases [6,7,30]. Our results also indicated that TNF-a-mediated smDC might be applicable to the RA treatment at least in animal models, and this claim was further supported by our detailed analysis of smDC-mediated immune reactions both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, some reports have demonstrated that DC are able to induce not only immunity but also immune tolerance, depending on the stage of their maturation. In fact, some papers have demonstrated that certain types of DC have potential for the treatment of autoimmune diseases [6,7,30]. Our results also indicated that TNF-a-mediated smDC might be applicable to the RA treatment at least in animal models, and this claim was further supported by our detailed analysis of smDC-mediated immune reactions both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 80%
“…The natural function of immature DC (iDC) is to create conditions for self-tolerance either via the generation of Treg or via the induction of apoptosis or anergy of autoreactive effector cells [4,5]. Moreover, some reports have demonstrated that tolerance is observed when partial-or semi-maturation of DC (semi-mature DC, smDC) occurs, whereas only fully matured DC (mDC) are immunogenic [6,7]. It has also been reported that in vitro-generated smDC, which were matured by TNF-a and intravenously injected into mice, functioned in a tolerogenic fashion via the prevention of Th1-dependent EAE, by inducing CD4…”
Section: Introductionmentioning
confidence: 99%
“…To date the tolerogenic capacity of TNF-DCs has also been shown in other autoimmune diseases like thyroiditis and rheumatoid arthritis (17,18). However, TNF-DCs pulsed simultaneously with MHC II-and MHC I-restricted peptides efficiently initiate CD8 T cell responses leading to autoimmune diabetes, despite the simultaneous induction of a protective IL-10-secreting CD4 ϩ T cell response (19). Thus, more detailed analyses regarding the immune response induced by TNF-DCs are needed.…”
mentioning
confidence: 99%
“…Однако дальнейшие исследования показали, что TNF-ДК, нагруженные одновременно пептидами, ограниченными MHC I и MHC II, делали толерантными Т-клетки CD4+, но не Т-клетки CD8 + . Прайминг Т-клеток CD8+ TNF-ДК был достаточен для индукции экспериментального аутоиммунного диабета [145]. Более того, подобно незрелым ДК, TNF-ДК не окончательно дифференцировались и могли становиться иммуностимуляторными в ответ на дальнейшую активацию сигналами созревания ДК [65,146].…”
Section: дендритные клетки (дк) (Dc)unclassified